The determinants that affect university students’ intention to use online recruitment platforms in Malaysia - Liong, Christine Siaw Fung; Teoh, Wevern (2022)
This study uses a conceptual framework that combines the technology acceptance model (TAM) and the theory of planned behaviour (TPB) to explore university students' intentions to use online recruiting platforms (ORP) in Malaysia. The respondents for this research are university students in Malaysia and 300 responses were collected. Partial least squares structural equation modelling (PLS-SEM) was used to examine the proposed hypothesis. The findings of the study demonstrated that there are significant relationships between partial relationship of the independent variable—subjective norm (SN), perceived behavioural control (PBC) and each moderator—perceived usefulness (PU), perceived ease of use (PEoU) as well as dependent variable— intention to use (INT) with each moderator (PU, PEoU). The discussions of the findings, research implications, limitations and recommendations are included. This research allows the researchers, ORP developers, talent recruiters and the government to gain new insights so that the demands and adoption level of the university students in the adoption of ORP can be met and raised.